Hypoxia and Temperature Regulated Morphogenesis in Candida albicans - Desai, Prashant R. (Public Library of Science, 2015)

(untitled) (PLoS Genet)
Candida albicans is a common commensal in the human gut but in predisposed patients it can become an important human fungal pathogen. As a commensal, C. albicans adapts to low-oxygen conditions and represses its hyphal development by the transcription factor Efg1, which under normoxia activates filamentation. The repressive hypoxic but not the normoxic function of Efg1 required its unmodified N-terminus, was prevented by phosphomimetic residues at normoxic phosphorylation sites T179 and T206 and occurred only at temperatures ≤35°C. Genome-wide binding sites for native Efg1 identified 300 hypoxia-specific target genes, which overlapped partially with hypoxic binding sites for Ace2, a known positive regulator of hypoxic filamentation. Transcriptional analyses revealed that EFG1, ACE2 and their identified targets BCR1 and BRG1 encode an interconnected regulatory hub, in which Efg1/Bcr1 act as negative and Ace2/Brg1 act as positive regulators of gene expression under hypoxia. In this circuit, the hypoxic function of Ace2 was stimulated by elevated CO(2) levels. The hyperfilamentous phenotype of efg1 and bcr1 mutants depended on Ace2/Brg1 regulators and required increased expression of genes encoding Cek1 MAP kinase and its downstream target Cph1. The intricate temperature-dependent regulatory mechanisms under hypoxia suggest that C. albicans restricts hyphal morphogenesis in oxygen-poor body niches, possibly to persist as a commensal in the human host.